KERAGAAN VARIETAS UNGGUL BARU PADI SAWAH DI KECAMATAN PULAU PUNJUNG KABUPATEN DHARMASRAYA, PROVINSI SUMATERA BARAT - Misran Misran (UIR Press, 2015)
Yielding variety is one of the important component technologies to increase production. Selection of varieties is suitable with a very supportive environment agro-ecosystem rice farming success. This research aims to determine the proper performance of growth and production of new superior varieties of lowland rice. The experiment was conducted at the farmers’ rice field Sikabau, Pulau Punjung, Dharmasraya Regency, from June to October 2012, using a randomized block design (RBD) with five replications. Treatment used three new varieties of lowland rice, i.e., Logawa, Tukad Unda, Mekongga and the high-yielding varieties of lowland rice of IR 66 which has evolved a long enough as a comparison. The seedlings was planted 3-5 seedlings/hill with spacing of 25 x 25 cm. Fertilizers applied is 300 kg Ponska, 100 kg urea and 30 kg KCl/ha. Data were collected consisted of plant height, maximum number of tiller/hill, number of productive tiller/hill, yield components and yield. The results showed that three new varieties of lowland rice, namely Logawa, Mekongga and Tukad Unda had good growth and yield. The new varieties which had a very good response were Logawa (5.8 t/ha), Mekongga (5.6 t/ha) and Tukad Unda (5.5 t/ha).